1998
DOI: 10.1203/00006450-199807000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Formula versus Breast Milk on Cholesterol Synthesis Rates in Four-Month-Old Infants

Abstract: We investigated whether supplementation of regular formula (RF) with cholesterol (Ch) (RF+Ch) influenced circulating Ch levels and de novo synthesis compared with their breast-fed (BF) counterparts in 4-mo-old infants. The incorporation rate of deuterium in body water into erythrocyte membrane-free Ch over 48 h was used as an index of cholesterogenesis. Plasma total-Ch and LDL-Ch concentrations were highest (p < 0.02) in BF infants, compared with infants in the RF-fed groups. Infants in the RF+Ch groups showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 62 publications
4
33
2
Order By: Relevance
“…The positive relationship between dietary cholesterol intake and serum lipid levels in the neonatal period is well established in both animal 4-10 and infant [11][12][13][14][15][16][17][18][19] studies. The higher HDL cholesterol levels exhibited by the MCF-fed infants (Table 4), compared with HM-and CF-fed infants, might be attributable in part to differences in the form of cholesterol in HM and MCF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The positive relationship between dietary cholesterol intake and serum lipid levels in the neonatal period is well established in both animal 4-10 and infant [11][12][13][14][15][16][17][18][19] studies. The higher HDL cholesterol levels exhibited by the MCF-fed infants (Table 4), compared with HM-and CF-fed infants, might be attributable in part to differences in the form of cholesterol in HM and MCF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous human infant studies showed a significant inverse relationship between dietary cholesterol and FSR at 4 months. [16][17][18][19] With deuterium incorporation methods, previous investigators estimated that endogenous cholesterol FSR ranged from 0.02 pools per day among breastfed infants to 0.11 pools per day among infants fed formulas with varying concentrations of cholesterol. The present study demonstrated an effect of infant diet on FSR at 4 months, with CF-fed infants having an up-regulated rate of endogenous cholesterol production, compared with HM-fed infants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the mass consumption of infant formula results in a reduction or replacement of breastfeeding, there is a risk for negative population level health outcomes (Chantry, Dewey, Peerson, Wagner, & Nommsen-Rivers, 2014;Schanler, 2015;Sethi, 2012). An increasing number of studies have identified potential associations between artificial formula consumption and poor health later in life, including autoimmune diseases, excess body weight, asthma, eczema and Type II diabetes (Bayley et al, 1998;Chandra, Puri, & Hamed, 1989;Gillman et al, 2001;Labiner-Wolfe et al, 2008;Patelarou et al, 2012;Slusser, 2007).…”
Section: Introductionmentioning
confidence: 99%